TAFRO syndrome requiring combined IL 6 and IL 1 inhibition: a case report - Sultan, Ahmad Wael; Grießhammer, Eva; Hinrichs, Carl; Trenkmann, Lars; Oschlies, Ilske; Hanitsch, Leif Gunnar; Haibel, Hildrun; Schneider, Thomas; Leistner, Rasmus (Frontiers in Immunology, 2026)
IntroductionTAFRO syndrome is a rare and severe variant of idiopathic multicentric Castleman disease (iMCD). The name-giving presentation is a combination of thrombocytopenia, anasarca, fever, reticulin fibrosis/renal dysfunction, and organomegaly. The disease’s complex but unspecific presentation shows overlapping features with hyperinflammation syndromes of infectious, malignant, or autoimmune origin. Here, we present a case of a young patient with iMCD TAFRO refractory to targeted IL-6 inhibition.Case descriptionA 21-year-old previously healthy male developed progressive systemic inflammation with fever, persistent generalized lymphadenopathy, bicytopenia, polyserositis, and renal failure. Infectious diseases and oncological and immunological workup within the first 6 months after symptom onset yielded an unclear hyperinflammatory syndrome. Subsequently, the patient was treated with IL-1 inhibition resulting in partial symptom relief. However, after a flare, the repeated lymph node histopathology showed immunohistochemical features of iMCD and the diagnosis iMCD TAFRO was established. The patient was then additionally treated with IL-6 inhibition. An attempt to switch to monotherapy with IL-6 inhibition resulted in another flare-up of the disease. This demonstrated the need for continued combined IL-6 and IL-1 inhibition. Under this combination therapy, the patient showed complete and stable remission, which persisted even after 12 months of follow-up.ConclusionThis case highlights the diagnostic and therapeutic challenges posed by iMCD TAFRO. In cases with refractory disease despite targeted IL-6 inhibition, additional IL-1 inhibition might pose a further treatment option.